Дотримання принципів академічної доброчесності в освітньо-науковому середовищі ЗВО (Педевтологія, 2023)
This article analyses the concept of academic integrity in terms of quality culture. The aim is to contribute to the competitiveness of European education by ensuring its quality through the awareness of the need to develop a culture and disseminate best practices in this area. It is widely acknowledged that academic integrity is currently facing a crisis, which can be attributed to the increasing availability and use of online information resources and technologies that allow for the free dissemination of intellectual property results to the Ukrainian scientific and educational community. The Guidelines for Higher Education Institutions to Support the Principles of Academic Integrity cover the mechanism for maintaining academic integrity in Ukraine. These guidelines are based on six main blocks and were developed as part of the SAIUP Project for Promoting Academic Integrity in Ukraine with the support of the US Embassy. The analysis of international experience demonstrates that developing practical skills for high-quality academic writing is a complex process that requires constant and persistent effort. This text considers and analyses the principles of successful academic writing training. Academic integrity is widely recognised as a fundamental aspect of personal development, character stability, and moral consistency. This text presents ways to improve academic integrity in the preparation of written works by higher education students.